Learning and Perception in Al-Tirmidhi's Psychology - Abdul Razak, Abdul Latif (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Learning and Perception in Al-Tirmidhi's Psychology